Family planning provider choice: Differentials and determinants a re-analysis of the 1993 PNDS and 1998 PNDHS - Lee, Nanette R. (Animo Repository, 2000)
The study seeks to identify and compare the sources of variations in the choice of family planning provider among currently married women of reproductive age in 1993 and 1998. Furthermore, it ascertained the factors that significantly determine the choice of family planning service delivery point.This study made use of the 1993 Philippine National Demographic Surveys (PNDS) and the 1998 Philippine National Demographic (Health) Surveys (PNDHS) data. Thus, it covered a representative sample of currently married women who were using contraceptives. It had 2,176 and 2,285 respondents from the 1993 and 1998 surveys, respectively.Comparison of the 1993 and 1998 data showed that: 1) there was no significant difference in the proportions of women utilizing the public and private sectors of FP services between 1993 and 1998, still the public sources predominated and 2) there were significant differences in the profile of the modern FP users, the public sector users and the private sector users over the years and 3) the sources of variations in 1993 and 1998 did not significantly differ, these include predisposing characteristics such as age, education, number of living children, method used, enabling characteristics such as employment status and wealth index, and community level attributes such as type of place and island of residence. Comparison of the users of the two types of FP provider revealed that private sector users were significantly more likely to be older, to be more educated, to have fewer children, to be users of limiting methods of contraception, to be employed, to be non-poor, to be urban dwellers and to come from NCR.When the effects of other variables were controlled, the study showed that predisposing, enabling and community-related attributes significantly determine the choice of family planning provider except for marital status and type of method availed. The likelihood of choosing the private sector is positively associated with age, education, employment status, wealth index and urban residence but negatively associated with number of living children. Moreover, the most likely users of this sector are women from NCR while the least likely users are women from Mindanao.Modern family planning users placed high value on geographic accessibility when choosing a family planning provider. Other reasons include absence of knowledge of other sources, quality of service and cost.